44th AIAA Aerospace Sciences Meeting and Exhibit 2006
DOI: 10.2514/6.2006-16
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Design and Analysis of High Performance Nozzles for Mach 4 Accelerator Vehicles

Abstract: The aerodynamic design and performance analysis of two exhaust nozzles considered for use on a vehicle following an accelerating flight profile to a maximum flight speed corresponding to Mach 4.2 is presented. The vehicle operational requirements were set by the Air Vehicle Baseline Study commissioned by the Office of Naval Research. An afterburning engine cycle was assumed in the design and analysis process. The two nozzles investigated here were an axisymmetric convergent-divergent (C-D) nozzle with variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, the overall length of the nozzle could not exceed 26 in. (5) CRITICAL PRESSURE (P*) (6) Critical flow through a convergent-divergent nozzle is a phenomenon that occurs when the mass flow rate of a gas cannot be increased when the pressure drop across the nozzle is further increased. The ratio between the downstream and upstream pressures at which this occurs is called the critical pressure ratio.…”
Section: Variable Geometry Convergent-divergent Nozzlementioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall length of the nozzle could not exceed 26 in. (5) CRITICAL PRESSURE (P*) (6) Critical flow through a convergent-divergent nozzle is a phenomenon that occurs when the mass flow rate of a gas cannot be increased when the pressure drop across the nozzle is further increased. The ratio between the downstream and upstream pressures at which this occurs is called the critical pressure ratio.…”
Section: Variable Geometry Convergent-divergent Nozzlementioning
confidence: 99%
“…This region of supersonic acceleration is terminated by a normal shock wave. (5) The shock can occur only in steady state when there is a supersonic flow. the gas has to pass through a converging-diverging nozzle to obtain a supersonic flow.…”
Section: Flow Behaviour In a Convergent-divergent Nozzlementioning
confidence: 99%
“…To incorporate compressibility effects in turbulence models, and consequently to better predict the decrease in the growth rate with increasing Mach number, an additional compressibility term should be included in the turbulence transport equations (Sarkar 1991;Sarkar et al 1991). and Georgiadis (2006) assessed the accuracy of modified two-equation turbulence models in flow field predictions of a subsonic (Mach number 0.5) heated and unheated jet. They showed that all the modified equations provided improved predictions compared to the standard models.…”
Section: Introductionmentioning
confidence: 99%
“…To incorporate compressibility effects in turbulence models, and consequently to better predict the decrease in the growth rate with increasing Mach number, an additional compressibility term should be included in the turbulence transport equations [10,11]. Georgiadis et al [12,13] assessed the accuracy of modified two-equation turbulence models in flow field predictions of a subsonic (Mach number 0.5) heated and unheated jet. They showed that all the modified equations provided improved predictions compared to the standard models.…”
Section: Introductionmentioning
confidence: 99%